2019
DOI: 10.1016/j.ymssp.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Finite element model updating using objective-consistent sensitivity-based parameter clustering and Bayesian regularization

Abstract: Finite element model updating seeks to modify a structural model to reduce discrepancies between predicted and measured data, often from vibration studies. An updated model provides more accurate prediction of structural behavior in future analyses. Sensitivity-based parameter clustering and regularization are two techniques used to improve model updating solutions, particularly for high-dimensional parameter spaces and ill-posed updating problems. In this paper, a novel parameter clustering scheme is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
(97 reference statements)
0
26
0
1
Order By: Relevance
“…To the authors' knowledge, this approach has not been previously used for evidence estimation in FE model updating and presents a step forward for deterministic model updating. Previous work by the authors implemented Bayesian regularization, but also optimized β, which is inappropriate for evidence estimation and model evidence comparison, as will be discussed below.…”
Section: Model Evidence Estimation and Bayesian Regularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors' knowledge, this approach has not been previously used for evidence estimation in FE model updating and presents a step forward for deterministic model updating. Previous work by the authors implemented Bayesian regularization, but also optimized β, which is inappropriate for evidence estimation and model evidence comparison, as will be discussed below.…”
Section: Model Evidence Estimation and Bayesian Regularizationmentioning
confidence: 99%
“…At this stage, the optimal value of β can be found by evidence maximization, giving β=false(mγfalse)false/false(2ErMPfalse), as in previous work, but this has several disadvantages. Foremost, the likelihood function will no longer be model‐independent since β will depend on the optimized model error ErMP.…”
Section: Model Evidence Estimation and Bayesian Regularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of this model updating technique also determined an optimal set of model parameters of the FE model; this minimized the differences between the measured properties and those of the FE model. A detailed explanation as to how the FE bridge model considered in this study was modified can be found in the authors' previous work, which focuses on developing algorithmic tools for sensitivity‐based parameterization methods and model updating techniques. Most model updating techniques are based on an underlying assumption that sensor measurements are deterministic so that they are used to infer the state of a structure (parameters of an FE model).…”
Section: System Identification and Fe Model Of A Major Long‐span Bridgementioning
confidence: 99%
“…In structural vibration modal analysis, the eigenvalue (square of frequency) and eigenvector (mode shape) are the two important parameters and their sensitivities are often used in many engineering problems such as structural vibration control [1][2][3][4][5][6], optimization design [7][8][9], model updating [10][11][12][13][14] and damage identification [15][16][17]. From the current research literature, the calculation formula of eigenvalue sensitivity is simple, but the calculating formula for eigenvector sensitivity is complicated.…”
Section: Introductionmentioning
confidence: 99%